A Deletion in the Endothelin-B Receptor Gene is Responsible for the Waardenburg Syndrome-Like Phenotypes of WS4 Mice - HORIBE, Akio; SHINKAI, Yusuke; TSUJI, Takehito; OHTANI, Shin; KUNIEDA, Tetsuo; KATAYAMA, Kentaro; MATSUSHIMA, Yoshibumi; TACHIBANA, Masayoshi (Experimental Animals, 2006)
The WS4 mouse is an animal model for human Waardenburg syndrome type 4 (WS4), showing pigmentation anomalies, deafness and megacolon, which are caused by defects of neural crest-derived cells. We have previously reported that the gene responsible for the WS4 mouse is an allele of the piebald mutations of the endothelin B receptor gene (Ednrb). In this study, we examined the genomic sequence of the Ednrb gene in WS4 mice and found a 598-bp deletion in the gene. The deleted region contains the entire region of exon 2 and the 5' part of exon 3 and is flanked by inverted repeat sequences which are suggested to trigger the deletion. We concluded that the deletion in the Ednrb gene is the causative mutation for the phenotype of WS4 mice.